Proceedings of the 25th ACM International on Conference on Information and Knowledge Management 2016
DOI: 10.1145/2983323.2983911
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Approaches to Controversy Detection

Abstract: Recently, the problem of automated controversy detection has attracted a lot of interest in the information retrieval community. Existing approaches to this problem have set forth a number of detection algorithms, but there has been little effort to model the probability of controversy in a document directly. In this paper, we propose a probabilistic framework to detect controversy on the web, and investigate two models. We first recast a state-of-the-art controversy detection algorithm into a model in our fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Controversy Analysis on the Web: To identify controversial topics in Web documents, some work has demonstrated that identifying relevant Wikipedia pages as well as building a controversy language model is effective [3,9,11]. Several studies then have formally defined a model for controversy detection [10,21].…”
Section: Related Workmentioning
confidence: 99%
“…Controversy Analysis on the Web: To identify controversial topics in Web documents, some work has demonstrated that identifying relevant Wikipedia pages as well as building a controversy language model is effective [3,9,11]. Several studies then have formally defined a model for controversy detection [10,21].…”
Section: Related Workmentioning
confidence: 99%
“…Identifying Quantifying Content Network Choi et al [8] Popescu and Pennacchiotti [45] Mejova et al [39] Klenner et al [33] Tsytsarau et al [49] Dori-Hacohen and Allan [14] Jang et al [29] Conover et al [10] Coletto et al [9] Akoglu [2] Amin et al [3] Guerra et al [27] Morales et al [40] Garimella et al [20] inside communities created by like-minded people, who reinforce and endorse the opinions of each other. This phenomenon has been quanti ed in many recent studies [4,18,26].…”
Section: Papermentioning
confidence: 99%
“…Garimella et al (2017) identified controversial topics using bipartite Twitter follower-graphs, while Dori-Hacohen and Allan (2015) proposed an incidentally supervised binary classification to predict controversial topics via Wikipedia tags. Jang et al (2016) used language modeling to predict controversial documents, based on earlier hypotheses by Cramer (2011): "that language in news discussions is a good indicator of controversy". Choi et al (2010) focused on using sentiment polarity indicators and subtopics, i.e.…”
Section: Related Researchmentioning
confidence: 99%